Assessment of Cochlear Synaptopathy with Standard Clinical Equipment - Lobdell, Anne; Trujillo, Tevan; Jennings, Skyler G. (Journal of the American Academy of Audiology, 2022)
Background Tinnitus, hyperacusis, and difficulties listening in background noise may be associated with the loss of auditory nerve fibers known as the condition of cochlear synaptopathy. Multiple research-based tests of auditory function have been developed to identify the potential for synaptopathy in animals and humans, including assessment of the middle-ear muscle reflex (MEMR). Despite these research-based tests, there is no verified method for measuring or identifying the potential for cochlear synaptopathy using standard audiologic equipment.Purpose The goal of this study was to determine if commonly used audiometric equipment could be configured in a way that approximated the test methods used in the research environment, making it a viable tool in the assessment of patients who present with symptoms consistent with cochlear synaptopathy (tinnitus, hyperacusis, speech-in-noise difficulties).Methods Laboratory-based and clinically based measures of MEMR strength—as estimated from changes in probe pressure/admittance in response to contralateral noise—were compared for 20 subjects. MEMR strength estimated from laboratory equipment increased with increasing intensity of the contralateral noise elicitor.Results and Conclusions A moderate positive correlation was found between laboratory- and clinically based measures of MEMR strength. This correlation supports the hypothesis that commonly used clinical equipment can be employed to assess the potential for cochlear synaptopathy in patients who present with the associated symptoms.
Keywords: acoustic reflex; synaptopathy; cochlear nerve degeneration; middle-ear muscles; hidden hearing loss